Allergen-Specific Immunotherapy in Patients 55 Years and Older: Results and Review of Literature - Baptistella,Eduardo (2013)
Introduction  Over the years the immune system suffers many morphologic and functional alterations, which result in a peak of function in puberty and a gradual decrease in the elderly. Aim  Treat patients 55 years or older with allergic rhinitis with immunotherapy and then analyze the response to allergens. Materials and Methods  From June 2009 to July 2010, 104 charts of patients 55 years or older with allergic complaints were evaluated. The patients were selected by anamnesis, physical examination, and otorhinolaryngologic exam. The patients had cutaneous test for mites before and after 1 year of sublingual specific immunotherapy. The cutaneous response was classified as negative (absent), light, moderate, or severe. Results  Before vaccination, 42 (40.4%) patients were classified as having a severe form of allergy and 62 (59.6%) as having a moderate allergy. After the specific therapy, 40 (38.4%) patients were classified as negative (absent), 37 (35.6%) as light, 19 (18.3%) as moderate, and 8 (7.7%) as severe responses. Conclusion  Immunotherapy, a desensitization technique, is indicated in cases which patients cannot avoid the exposure to allergens and in situations where pharmacologic therapy is not ideal. Specific immunotherapy to treat the allergic rhinitis in elderly patients was efficient and had no collateral effects, and in addition to the clinical benefit, improvement in the cutaneous test could also be observed.